Intranasal administration of Acinetobacter lwoffii in a murine model of asthma induces IL‐6‐mediated protection associated with cecal microbiota changes. Issue 5 (11th December 2022) - Alashkar Alhamwe, Bilal; Gao, Zhan; Alhamdan, Fahd; Harb, Hani; Pichene, Matthieu; Garnier, Abel; El Andari, Jihad; Kaufmann, Andreas; Graumann, Peter L.; Kesper, Dörthe; Daviaud, Christian; Garn, Holger; et al.
Abstract: Background: Early‐life exposure to certain environmental bacteria including Acinetobacter lwoffii ( AL ) has been implicated in protection from chronic inflammatory diseases including asthma later in life. However, the underlying mechanisms at the immune‐microbe interface remain largely unknown. Methods: The effects of repeated intranasal AL exposure on local and systemic innate immune responses were investigated in wild‐type and Il6 −/−, Il10 −/−, and Il17 −/− mice exposed to ovalbumin‐induced allergic airway inflammation. Those investigations were expanded by microbiome analyses. To assess for AL ‐associated changes in gene expression, the picture arising from animal data was supplemented by in vitro experiments of macrophage and T‐cell responses, yielding expression and epigenetic data. Results: The asthma preventive effect of AL was confirmed in the lung. Repeated intranasal AL administration triggered a proinflammatory immune response particularly characterized by elevated levels of IL‐6, and consequently, IL‐6 induced IL‐10 production in CD4 + T‐cells. Both IL‐6 and IL‐10, but not IL‐17, were required for asthma protection. AL had a profound impact on the gene regulatory landscape of CD4 + T‐cells which could be largely recapitulated by recombinant IL‐6. AL administration also induced marked changes in the gastrointestinal microbiome but not in the lung microbiome. By comparing the effects on the microbiota according to mouse genotype and AL ‐treatment status, we have identified microbial taxa that were associated with either disease protection or activity. Conclusion: These experiments provide a novel mechanism of Acinetobacter lwoffii ‐induced asthma protection operating through IL‐6‐mediated epigenetic activation of IL‐10 production and with associated effects on the intestinal microbiome. Abstract : This study confirms that IL‐6‐deficient mice are resistant to asthma‐protective effect driven by Acinetobacter lwoffii ( AL ). Downstream of IL‐6, the asthma‐blocking properties is mediated by IL‐10, but not IL‐17. In IL‐6‐deficient mice, exposure to AL increases Muribaculaceae and Sutterellaceae, and decreases Lachnospiraceae and Bacillaceae, compared to the unexposed mice, restoring the status quo observed in the wild‐type littermates mice. In vitro experiments demonstrate modulations in the epigenetic landscape of histone mark H3K27ac at the promoter regions of the Il10 pathway‐related genes ( Mapk1/3, Stat3, and c‐MAF ) in the CD4 + T‐cells cultured with AL ‐conditioned macrophage supernatant ( AL ‐Mφ). These changes were reversed by anti‐IL‐6 treatment ( AL ‐Mφ + anti‐IL‐6) and phenocopy by adding rIL‐6 alone.Abbreviations: AL, Acinetobacter lwoffii ; AL ‐Mφ, AL ‐conditioned macrophage; c‐Maf, c‐musculoaponeurotic fibrosarcoma transcription factor; IL, interleukin; Il6 −/−, Il6 knockout; Il10 −/−, Il10 knockout; Mφ, macrophages; Mapk1/3, mitogen‐activated protein kinase 1/3 ; rIL‐6, recombinant IL‐6; Stat3, signal transducer and activator of transcription 3; TNF, tumor necrosis factor; WT, wild‐type